السنن الکبرٰی کی ترتیب و تدوین میں امام نسائی ؒ کا منہج و اسلوب (ایک تحقیقی جائزہ): Methodolgy of Imam nasai in his book as sunan ul Kubra - Muhammad Javid (MEI, 2023)
Almighty Allah revealed his last book for the guidance of humanity on his last prophet Hazrat Muhammad( paece be upon him )and said that it is duty of prophet( peace be upon him) to explain the contents of Holy Quran.Prophet (peace be upon him) himself motivated his companions to note his sayings (Ahadith).Many companions of Holy Prophet (peace be upon him) and scholars(muhaddithin)afterwards noted, collected and compiled their books on Ahadith.Imam Nasai R.A is one of them who wrote many books on Hadith & its relevent fields. Al Sunan ul kubra is one of the Nasai,s books.He wrote it at first and then summarised his famous book Al-Mujtaba from it, which is taught almost in all the madaris of Pakistan.Al Sunan ul kubra has 11949 ahadith in it.Beside this it has a precious treasure of "Uloom ul Hadith".This book also clears many misconceptions about Imam Nasai,s manhaj & beliefs. This article enlightens many aspects of Al Sunan ul Kubra and methodology of Imam Nasai.It also indicates towards the conditions that author adopted during the copmilation of his great book As Sunan ul Kubra.